Evaluation of the FilmArray Gastrointestinal Panel on Health Care Utilization in Immunocompetent Adults Presenting to the Emergency Department with Non-Clostridium difficile Acute Gastrointestinal Infection. (4th October 2017) - Cubillos, Ashley; Turner, Edgar; Saunders, Mary Beth; Estrada, Sandy
Abstract: Background: Multiplex polymerase chain reaction (PCR) rapid diagnostic technologies, such as the FilmArray Gastrointestinal (GI) Panel, have the potential to quickly determine the microbiologic etiology of acute gastrointestinal illnesses and prevent additional healthcare utilization through further diagnostic tests. However, the utility of this diagnostic on clinical management in patients with these illnesses remains unclear. This study compares health care utilization for patients where GI panel testing was performed in the emergency department (ED) vs. patients where conventional stool diagnostic methods were utilized. Methods: This retrospective cohort study included adults presenting to hospital EDs and diagnosed with an intestinal infectious disease. Exclusion criteria included: immunocompromised state, C. difficile positive by PCR, and chronic diarrheal illness. Rate of hospital admission, total healthcare length of stay, use of diagnostic imaging, identification of pathogen, 30-day readmission for diarrhea, and mortality were compared between patients receiving a GI panel diagnostic test and those not receiving the test. Results: A total of 100 patients were included in each group. Rates of hospital admission were numerically higher in the GI panel group (23% vs. 14%, P = 0.10). Time spent in the ED was longer in the GI panel group (4.3 vs. 3.4 hours, P <0.001) however total time in hospital was shorter (2.2 vs. 4.0 days, P  = 0.04). A pathogen was identified in 91% of GI panel patients vs. 5% of patients not receiving the test ( P <0.001). Abdominal computerized tomography scans were more frequently obtained in the GI panel group (42% vs. 29%, P  = 0.05). The rate of 30-day emergency department presentation or readmission for diarrhea was similar between groups, and 30-day mortality was zero in each group. Conclusion: Patients with a positive GI panel were more likely to have a pathogen identified, undergo diagnostic imaging, and be admitted from the ED, although their length of stay was significantly shorter. Further study is needed to determine the appropriateness of healthcare utilization and cost-benefits with use of the GI panel in the emergency department as well as impact on antimicrobial utilization. Disclosures: All authors: No reported disclosures.